Factors Affecting Performance of Agricultural Value Chains: The Case of Small-Scale Coffee Marketing In Kangundo, Machakos County - Kundu, Ruth N.; Ngigi, Marther W. (Machakos University, 2018)
Coffee is Kenya's forth source of foreign exchange after tourism, tea and horticulture, and significantly contributes to farm income and employment. The different marketing systems in the producer and marketing cooperatives (P&MCs), which ensure unsatisfying returns, poses a great challenge to the coffee industry, which comprises majority of small-scale producers (SSPs). The study sought to determine the factors influencing coffee marketing by small-scale producers and to assess the influence of smallholder coffee marketing systems to the coffee value chain. The study employed descriptive design. The establishment under study features small-scale coffee producers in Kangundo Sub-County, Machakos County. Questionnaires were used to gather Primary data. Stratified Sampling technique was used to compare the views of SSPs and top management of P&MCs on the target objectives. Statistical Program for Social Sciences (SPSS) aided analysis of quantitative data, while content analysis helped analyze qualitative data. Key challenges facing coffee marketing were low and delayed pay to SSPs, poor management of P&MCs, and low education levels of top management of P&MCs and SSPs. Smallholder coffee marketing systems in turn affects coffee value chain through financial constraints, reduced returns and reduced production. Policy implications of these findings through complementary education programs for SSPs and P&MCs and intervention of cooperatives' management through the relevant government institutions is the need for creating awareness of suitable and affordable measures towards an enhanced sustainable system in the Coffee Industry.
Keywords: Coffee Value Chain; Small-Scale Producers; Machakos County; Marketing; Producer and Marketing Cooperatives